2009
DOI: 10.1177/1065912908329355
|View full text |Cite
|
Sign up to set email alerts
|

The Electoral Benefits of Distributive Spending

Abstract: Prior studies search for evidence that distributive spending influences Congress members’ vote shares but find limited evidence. The authors argue that Democratic and Republican members each benefit from different types of distributive projects. Democrats benefit from delivering spending projects (what most people think of as “pork”) to their constituents, while many Republican members benefit from delivering contingent liabilities (in which the federal treasury underwrites a private entity’s financial risk). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 19 publications
1
46
1
Order By: Relevance
“…There are two possible reasons why we might uncover this result. First, prior research has found Republicans tend not to benefit from this type of federal spending so the largely null result here should not be too surprising ( 1997; Lazarus & Reilly, 2010;Sellers, 1997). Second, although the majority leadership has a strong incentive to maintain its majority and the power that goes along with it, cardinals and ranking members tend to be powerful independent of majority status.…”
Section: Resultsmentioning
confidence: 71%
“…There are two possible reasons why we might uncover this result. First, prior research has found Republicans tend not to benefit from this type of federal spending so the largely null result here should not be too surprising ( 1997; Lazarus & Reilly, 2010;Sellers, 1997). Second, although the majority leadership has a strong incentive to maintain its majority and the power that goes along with it, cardinals and ranking members tend to be powerful independent of majority status.…”
Section: Resultsmentioning
confidence: 71%
“…Federal spending may provide important information about how well administration policies are responding to the 7 For a further discussion of credit sharing in the context of multiple representatives, see Schiller (2000), Chen (2010), and Shepsle et al (2009). needs of a voter's community. However, whether an individual voter is inclined to support increased federal spending may also be a function of that individual's ideological preferences (Haselswerdt and Bartels 2011;Lazarus and Reilly 2010;Sidman and Mak 2006). Specifically, conservative voters may be less inclined to reward federal spending than liberal voters.…”
Section: Voters and Federal Spendingmentioning
confidence: 99%
“…3 Several studies do find evidence of electoral effects from spending among certain types of incumbents and voters (e.g. Alvarez and Saving 1997;Alvarez and Schousen 1993;Lazarus and Reilly 2010). (Berry, Burden, and Howell 2010;Larcinese, Rizzo, and Testa 2006).…”
mentioning
confidence: 99%
“…22 It is highly surprising that with a history of clientelistic politics, such renaming of government programmes is not prohibited by law in Mexico, unless such 'branding' is of course aimed at eliciting 'gratitude' from beneficiaries. 23 It ranges from work on the impact of general spending by incumbents (e.g., Levitt and Snyder, 1997;Litschig and Morrison, 2012), and the closely related literature on 'redistributive politics' (e.g., Cox, 2004;Cox and McCubbins, 1986;Lindbeck and Weibull, 1987;Dixit and Londregan, 1996), to the work that looks at the impact of specific categories of spending such as campaign spending (Jacobson, 1990;Levitt, 1994), 'earmarks' (Lazarus and Reilly, 2010;Pop-Elches and Pop-Elches, 2008), and specific programmes (Curto-Grau, 2017; Lazarus et al , 2012;Cruz and Schneider, 2017;Healy and Malhotra, 2009). The literature has also covered questions related to individual voters' income (often referred to as 'pocketbook voting' (Grafstein, 2009;Kramer, 1983); the effects of economic conditions in general, as opposed to partisanship, ideology, or social status (Lewis-Beck and Stegmaier, 2000), and within that strand, studies that examine whether voting is retrospective or prospective (Fiorina, 1978;Fair, 1996;Healy and Malhotra, 2013;Lockerbie, 1991).…”
Section: Theoretical Modelmentioning
confidence: 99%